Peran Musik Tradisi pada Pengembangan Kemampuan Berpikir Kognitif Siswa Sekolah Dasar - Jarmani Jarmani (Journal on Education, 2024)
This study aims to analyze the role of traditional music in developing the cognitive thinking abilities of elementary school students. It employs a qualitative method through literature review. The findings indicate that traditional music offers numerous benefits for enhancing the cognitive thinking abilities of elementary school students, including improving memory and concentration, fostering creative and logical thinking skills, enhancing problem-solving abilities, improving communication skills, and enhancing critical thinking skills. The study also suggests several ways to integrate traditional music into elementary school education, such as incorporating it into Language and Culture lessons, teaching Traditional Music Arts, offering music extracurricular activities, implementing creative projects, and collaborating with the local community. In conclusion, traditional music can play a significant role in the development of cognitive thinking abilities among elementary school students. Integrating traditional music into education can contribute to the holistic development of students.